Complexities in identifying seed storage behavior of hard seed-coated species: a special focus on Lauraceae. Issue 1 (2nd January 2019) - Jaganathan, Ganesh K.; Li, Jiajin; Yang, Yashu; Han, Yingying; Liu, Baolin
ABSTRACT: Seeds are broadly grouped into orthodox (desiccation-tolerant), intermediate and recalcitrant (desiccation-sensitive) based on their ability to withstand drying. Whilst the protocols developed to classify seeds into one of the three groups have aided ex-situ storage of germplasm, the classification of many species with seeds having a hard coat appears to be perplexing. Using Lauraceae as a model family, we address the possible reasons for this confusion. We collected data available in the literature on Lauraceae and found 30 species studied that were respectively assigned to orthodox (3 species), intermediate (4 species) or recalcitrant (23 species) groups. In addition, another 16 species (2 orthodox and 14 recalcitrant) were doubtfully classified and 6 species were labeled as uncertain. We speculate a hard seed coat found in many of Lauraceae species present substantial challenge in seed desiccation studies and identified five key problems including (1) inferring storage behavior without conducting desiccation-sensitivity assessment to evaluate the germination ability of seeds by drying to low moisture contents; (2) seed storage behavior was determined by germinating the seeds after partial drying and storing at various temperatures, e.g. 0 or −18°C; (3) seeds that failed to germinate at narrow range of temperatures and light conditions were concluded as dead, without considering the possibility that they might be dormant; (4) culminating germination studies quickly, sometimes within few days; and (5) not testing the drying ability of seeds without seed coat. We highlight that addressing these issues would lead to accurate categorization of seed storage behavior that can ensure better seed storage practices.